IMPLEMENTASI UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK (Studi Kasus Penanganan Anak Korban Tindak Kekerasan di Kabupaten Nagan Raya) - Nila Trisna; Ida Zulbaidah (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
In Law Number 35 Year 2014 concerning Child Protection Article 1 Paragraph (1) explains that a child is someone who is not yet 18 (eighteen) years old. Forms of violence against children are classified into physical, psychological, sexual and social violence. The violence can occur due to several factors including family vulnerability, economic factors, educational factors, socio-cultural factors, and environmental factors. The number of cases of violence against children requires comprehensive treatment. Handling given not only to victims but also to perpetrators, this study uses normative juridical methods and Empirical Juridical This study uses normative legal research methods, therefore the study is prescriptive The approach used in this study, namely the legislative approach state approach, and conceptual approach, the research material is analyzed with a qualitative approach, with the aim to understand the meaning of the legal material that has been collected, which is then interpreted normatively, logically and systematically using inductive methods. Keywords: Implementation, Children, Violence